Virtual-Based Aquatic Plyometric Training: How it Effects Lower Extremity Muscle Strength? - Viktor Simanjuntak; Edi Setiawan; Novi Yanti; Yudha Isnaini Lalu Moh; Mashuri Eko Winarno (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
The low achievement of long jump athletes and the limited virtual-based aquatic plyometric exercises to increase lower extremity muscle strength are the gaps in this study. This study aims to increase lower extremity muscle strength of long jump athletes through virtual-based plyometric aquatic training. This research adopted a mixed methods research. This study involved participants from long jump athletes at the University of Tanjung Pura in Indonesia (n = 20). Participants were divided into two groups, namely an experimental group (n = 10) and control group (n = 10). The quantitative instrument involved a leg dynamometer for measuring lower extremity muscle strength. While, the qualitative instrument used in-depth interview. Quantitative data analysis was carried out through IBM SPSS to calculate descriptive statistics and normality, while the paired sample t-test to test differences in lower extremity muscle strength values in the experimental and control groups. Qualitative analysis was carried out through recording, describing and coding stages, which categorized into three themes. Based on quantitative results, it showed that virtual-based plyometric aquatic training was proven significantly increase lower extremity muscle strength (ps0.05), but there was no significant effect in the control group (p & 0.05). Qualitative results found out that most of the participants gave a positive opinion regarding virtual-based plyometric aquatics. Thus, this study confirms that virtual-based plyometric aquatic training can be used to increase lower extremity muscle strength.